Legal Aspect of Copyright Transfer by Early Childhood - Mukaromah, Dwi Asri; Dewi, Cokorde Istri Dian Laksmi (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Valuable possessions or inheritances are objects that can be inherited, inheritance in this case is not only about tangible objects such as land, houses, jewelry, and so on, but works of art are also the inheritance rights of the creator that can be inherited. to his family. This article applies normative juridical research methods to analyze the copyright transfer process and identify its implications for Article 1320 of the Civil Code. Research highlights that while copyright is transferable, such actions can violate positive legal provisions. As a result, this study offers a new perspective on the conflict between copyright transfer and existing legal norms, providing a basis for a rethink of relevant regulations. The implications of these findings could impact on further understanding of the relationship between copyright, inheritance, and legal protection of minors.